Evaluasi Permintaan Penumpang Angkutan Udara Rute Jakarta - Denpasar Terhadap Berubahan Tarif - M. Herry Purnama (WARTA ARDHIA, 2010)
Demand for trarsport is influenced by many factors either directly related to transport or not. These factors are always changing along with the dynamics of society and the passage of time. One of the factors that affect to air transport demand is the change in tariffs. By using exponential regression will know the level of of demand for passenger air transport Denpasar-Jakarta. The results showed that elasticity of the Jakarta-Denpasar flight route of -0.082.Factors affecting the air transport made choice is a quick time by 85% to be the dominant factor, followed by 12.1% comfort of a Cheap rate 2.82% and no one chose the factor of safety. Alternative modes of choice or a replacement in case of air freight rate increase on every presentaseperubahan fare to Denpasar-Jakarta route passengers will switch to buses.